Impact of NRTI resistance mutations on virological effectiveness of antiretroviral regimens containing elvitegravir: a multi-cohort study. (11th October 2019) - Modica, Sara; Redi, David; Gagliardini, Roberta; Giombini, Emanuela; Bezenchek, Antonia; Di Carlo, Domenico; Maggiolo, Franco; Lombardi, Francesca; Borghetti, Alberto; Farinacci, Damiano; Callegaro, Annapaola; Gismondo, Maria R; et al.
Abstract: Background: Antiretroviral drug resistance mutations remain a major cause of treatment failure. Objectives: To evaluate the impact of NRTI resistance mutations on virological effectiveness of elvitegravir-containing regimens. Materials and methods: We selected treatment-experienced HIV-1-infected patients starting elvitegravir/cobicistat/emtricitabine/tenofovir alafenamide (E/C/F/TAF) or elvitegravir/cobicistat/emtricitabine/tenofovir disoproxil fumarate (E/C/F/TDF), with at least one protease/reverse transcriptase genotype available before switching and at least one HIV-1 RNA viral load (VL) measurement during follow-up. The primary endpoint was virological failure (VF), defined as one VL value of ≥1000 copies/mL or two consecutive VL values of >50 copies/mL. Results: We included 264 ART regimens: 75.6% male, median (IQR) age 47 years (39–53), 7 years (3–16) of HIV infection, nadir CD4+ 247 cells/mm 3 (105–361), 81.5% with VL ≤50 copies/mL and 11.7% with at least one NRTI mutation at baseline. Eleven (5.2%) VFs occurred in virologically suppressed patients versus eight (15.1%) in viraemic patients. The estimated probability of VF at 48 weeks with versus without any NRTI mutation was 7.4% (95% CI 2.3–12.5) versus 3.8% (2.1–5.5) in virologically suppressed patients and 66.7% (39.5–93.9) versus 11.2% (6.5–15.9) ( P <0.001) in viraemic patients. The only predictor of VF was time on therapy (per 1 year more, adjusted HR 1.14, 95% CI 1.02–1.27, P =0.024) in viraemic patients. Conclusions: A switch to E/C/F/TDF or E/C/F/TAF is safe for virologically suppressed patients without documented NRTI resistance, but not recommended in viraemic patients with a history of NRTI resistance. Although we did not detect a detrimental effect of past NRTI resistance in virologically suppressed patients, a fully active regimen remains preferred in this setting due to possible rebound of drug-resistant virus in the long term.